The Impact of Foreign Remittancies on Armenia’s Economy Withinthe Context of the Russian-Ukrainian War Spillovers - Sargsyan, Karen (ՀՀ ԳԱԱ)
Although in modern economic realities, foreign remittances are an important source of financing for low- and middle-income countries, a clear consensus on their impact on the country's economic growth has not yet been formed. There are two main opposing views on this issue. A group of studies confirms that at the macroeconomic level, foreign remittances often contribute to economic growth by providing a significant source of foreign exchange inflows, increasing national income and aggregate demand, financing imports, and improving the balance of payments. At the same time, some authors draw attention to the negative impact of private foreign remittances on the country's economy, in particular, the loss of competitiveness of export-oriented sectors, the strong dependence of the economy on foreign transfers, the outflow of resources from the manufacturing sector to the service sector, the deterioration of the balance of payments, as well as the increase in the inflation rate. After the ongoing of the Russian-Ukrainian conflict, the volume of foreign private remittances inflows in the Republic of Armenia has sharply increased since the second quarter of 2022, due to new financial and economic realities in Russia and the economic and financial sanctions imposed on it by Western countries. This led, in particular, to a rapid growth in private consumer spending in the short term, which in turn stimulated economic activity in non-exportable sectors of the Armenian economy, such as trade, construction, and services. Analyzing the dynamics of the indicators of net flows of external private transfers and the rates of economic growth in Armenia, it becomes quite obvious that in the years of high economic growth in the Republic of Armenia, a high growth of private external transfers was also recorded, and in the years when foreign private transfers decreased, economic growth was quite low or an economic decline was recorded. Accordingly, it can be concluded that the economic growth of the Republic of Armenia continues to be largely determined by the growth of non-exportable sectors stimulated by external factors, in which case, in the event of a decrease in the impact of external factors, economic growth sharply slows down or even declines. Meanwhile, if economic growth were determined by the growth of export sectors, such as manufacturing and agriculture, then dependence on external financial resources would be weaker, and economic growth would be more stable. Թեև ժամանակակից տնտեսական իրողություններում արտաքին տրանսֆերտները ֆինանսավորման կարևոր աղբյուր են ցածր և միջին եկամուտ ունեցող երկրների համար, երկրի տնտեսական աճի գործում վերջիններիս ազդեցության վերաբերյալ հստակ կոնսենսուս դեռ չի ձևավորվել ։ Այս հարցում հիմնականում առկա են երկու հակադիր տեսակետներ ։ Ուսումնասիրությունների մի խումբ հավաստում է, որ մակրոտնտեսական մակարդակում արտաքին տրանսֆերտները (դրամական փոխանցումները) հաճախ նպաստում են տնտեսական աճին` ապահովելով արտարժույթի ներհոսքի զգալի աղբյուր, ավելացնելով ազգային եկամուտն ու համախառն պահանջարկը, ֆինանսավորելով ներմուծումը և բարելավելով վճարային հաշվեկշիռը: Միևնույն ժամանակ որոշ հեղինակներ ուշադրություն են դարձնում երկրի տնտեսության վրա մասնավոր արտասահմանյան տրանսֆերտների բացասական ազդեցությանը, մասնավորապես՝ արտահանմանն ուղղված ոլորտների մրցունակության կորստին, տնտեսության ուժեղ կախվածությանը օտարերկրյա փոխանցումներից, ռեսուրսների արտահոսքին արտադրական հատվածից դեպի սպասարկման ոլորտ, վճարային հաշվեկշռի վատթարացմանը, ինչպես նաև գնաճի մակարդակի աճին ։ Ռուս-ուկրաինական հակամարտության մեկնարկից հետո՝ 2022 թվականի 2-րդեռամսյակից Հայաստանի Հանրապետությունում կտրուկ ավելացել են օտարերկրյա մասնավոր տրանսֆերտների ներհոսքի ծավալը՝ Ռուսաստանում ձևավորված ֆինանսատնտեսական նոր իրողությունների և վերջինիս հանդեպ արևմտյան երկրների կողմից կիրառված տնտեսական ու ֆինանսական պատժամիջոցների պատճառով ։ Դա կարճաժամկետ ժամանակահատվածում առաջացրեց, մասնավորապես, մասնավոր սպառողական ծախսերի առաջանցիկ աճ, որն իր հերթին խթանեց տնտեսական գործունեությունը Հայաստանի տնտեսության ոչ արտահանելի հատվածներում, ինչպիսիք են առևտուրը, շինարարությունը և ծառայությունները: Վերլուծելով արտաքին մասնավոր տրանսֆերտների զուտ հոսքերի ցուցանիշների և Հայաստանում տնտեսական աճի տեմպերի դինամիկան միանգամայն ակնհայտ է դառնում, որ Հայաստանի Հանրապետությունում բարձր տնտեսական աճի տարիներին արձանագրվել է նաև մասնավոր արտաքին տրանսֆերտների բարձր աճ, իսկ այն տարիներին, երբ արտասահմանյան մասնավոր տրանսֆերտները նվազել են, տնտեսական աճը բավականին ցածր է եղել կամ գրանցվել է տնտեսական անկում ։ Ըստ այդմ, կարելի է եզրակացնել, որ Հայաստանի Հանրապետության տնտեսական աճը շարունակում է մեծապես պայմանավորված լինել արտաքին գործոններով խթանվող ոչ արտահանելի ոլորտների աճով, ինչի պարագայում արտաքին գործոնների ազդեցության նվազման դեպքում տնտեսական աճը կտրուկ դանդաղում է կամ նույնիսկ անկում է գրանցվում ։ Մինչդեռ, եթե տնտեսական աճը պայմանավորված լիներ արտահանվող ոլորտների աճով, ինչպիսիք են մշակող արդյունաբերությունը և գյուղատնտեսությունը, ապա արտաքին ֆինանսական ռեսուրսներից կախվածությունն ավելի թույլ կլիներ, իսկ տնտեսական աճը՝ ավելի կայուն ։
Keywords: Economics